Self Regulation and Sexual Behavior in Adolescent Visitors - Ezra Kristina Silitonga; Nuzsep Almigo (Faculty of Psychology, Universitas Semarang, 2023)
The research aims is to determine the relationship between self-regulation and sexual behavior among teenage visitors to PT. Jakabaring Sport City Palembang. The total population in this study was 150 teenage visitors and the samples were 105 teenage visitors to PT. Jakabaring Sport City obtained through purposive sampling technique. The measuring instruments used in this research are the self-regulation and sexual behavior scales. For analysis techniques, use simple regression analysis techniques. The results of research data analysis using the SPSS version 25 for Windows program show a correlation coefficient (R) of -0.433, a coefficient of determination (R square) of 0.188 and a p value = 0.000 (p<0.01). This shows that there is a negative relationship between self-regulation and sexual behavior among teenage visitors to PT. Jakabaring Sport City. The contribution of the two independent variables to the dependent is 18.8%.Keywords: self regulation, sexual behavior, adolescent